The Role of Lembaga Gemawan (NGO) Encouraging Women's Political Participation in West Kalimantan - Akhmad Rifky Setya Anugrah; Annisa Dina Amalia; Syarifah Nurma Afhiani; Ira Patriani; Eka Apriyani (Political Science Program, Universitas Negeri Semarang, 2023)
Women’s participation in political activities in Indonesia has grown since the reformation era in 1998. Democracy believes everyone has an equal right to participate in politics, and no one is left behind. The affirmative policy regarding women's participation in politics has been regulated in Article 65, paragraph (1) of Constitution No 12 of 2003, which mentions that at least 30% of parliament members should involve women as representatives. However, in reality, many cases show that women always become a second party with the privilege to participate in politics. Lembaga Gemawan is one of the local NGOs in West Kalimantan which focuses on women's empowerment, including political participation. This article discusses the role of the NGO (Lembaga Gemawan) in encouraging women's participation in local politics in West Kalimantan. This research used a descriptive qualitative method. The research results show that the Gemawan Institute has a positive role in encouraging women's participation in local politics in West Kalimantan through two strategies, 1) establishing empowered women's communities at the local level, such as the Mempawah Regency Women's Union (SPKM) and the Kayong Utara Regency Women's Union (SETARA); 2) organized a strategic course on winning women candidates at the provincial level by providing political education for women candidates.